FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA DI PT. X, DESA JLADRI, KECAMATAN BUAYAN, KABUPATEN KEBUMEN, JAWA TENGAH - Vidya Natalia Eka Putri; Anik Setyo Wahyuningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
PT. X in Kebumen, Central Java contributed to the number of work accidents in the mining sector. There is 1 case of work accident in the stock pile area. From the 2019 statistic report at PT. X, there are 2 cases of work accidents. In the 2020, there are 5 work accidents in the production section. In the 2021, there are 2 cases of work accidents. This study aims to determine the existence of factors related to work accidents at PT. X. This research is analytic observational research with quantitative approach and cross sectional study design. The research used 31 samples and used a total sampling technique. The instrument used is a questionnaire. Using chi-square test for analyze. The results showed that there was a correlation between knowledge (p = 0.042), years of service (p = 0.018), use of PPE (p = 0.047), and work supervision (p = 0.047 with work accidents. There was no correlation between age (p = 0.192) and education (p=0,226) with work accidents.The recommendation are conduct a safety talk or toolbox meeting before work, make a routine training on work safety and work safely, give rewards to workers, and provide supervisors more than 1 person.